Implementation of Sales Executive Dashboard for A Multistore Company in Yogyakarta - Halim Budi Santoso; Priyanka Ayu Sonia Putri; Budi Sutedjo Dharma Oetomo (Universitas Multimedia Nusantara, 2017)
Information Technology is a part of strategic part for enterprise strategic planning. Information Technology can help the enterprise to determine its strategic planning. Through data from the past, thecompany can learn something and help to decide some strategic issue. A Multistore Company in Yogyakarta has more than five stores. The problem raises to generate real-time sales reporting. Sales manager and owner do not have access to real-time sales condition. To ease management analyzing and reporting sales condition, dimension model of the sales data needs to be built. This dimension model will help to make executive report from some dimensions mentioned in data warehouse. Sales data will pass through some processes: Extract, Transform, and Load (ETL) in order to prepare the data warehouse. This process is preprocessing data before dimensional model is built. In this research multi-dimensional modelling by taking data from 3 stores ranging from 1 February 2014 to 31 January 2015. By implementing sales executive dashboard, it helps to monitor and analyze sales condition. Dashboard shows graphic which ease user, especially sales manager and owner to learn current and updated sales condition based on dimensions: time, outlet / store, and product. Report gives detail information and multidimensionalhelps to analyze data from different perspective. Index Terms—Dashboard, Multi Dimentional Model, ETL, Executive Reporting REFERENCES[1] W. Eckerson, Performance Dashboard: Measuring,Monitoring, and Managing Your Business, New Jersey: JohnWiley & Sons, 2011. [2] O. Romero and A. Abello,